The effect of shot peening on the initiation of fatigue cracks by fretting - Leadbeater, G. (1983)
Plain fatigue and fretting fatigue studies have been carried out on an Al - 4% Cu - 1% Mg alloy in various heat treated conditions. It has been determined that shot peening the surface results in substantial improvements in plain fatigue and fretting fatigue strengths. The major cause of the improvement of these properties is the presence of compressive stresses that are induced in the surface by the shot peening process. Surface roughening and work hardening of the surface are also caused by the shot peening process but these have little or no effect on the fretting fatigue properties.